Contesting Crimmigration in Post-hukou China - Ma, Tian (Springer International Publishing, 2022)
This book focuses on the criminalization trend and process regarding the internal migration in contemporary China from the perspective Law-in-Action. In Chinese society today, internal migrants are commonly perceived as criminals. Crimmigration, a global term that communicated the convergence of the criminal legal system and the immigration enforcement system, manifest itself in China's hukou-based (also known as the household registration system) criminal legal system. How hukou has been constructed into the concept of Crimmigration in China strikes at the core of the ultimate questions of this book: who is being criminalized, how does the political-economic-cultural institution known as 'hukou' shape the criminal justice process, and how has the role of hukou changed over time in the ever-changing process? Drawing on interviews with migrant leaders, police, prosecutors, criminal lawyers & judges, and prison staff in Yangtze River Delta, China, this book reflects on a historical development on hukou and its function in social control. Each chapter contributes to an extended analysis of pragmatic aspects of decision-making moments in the criminal justice system. This book will appeal to criminology researchers and students with in interest in law, politics, migration, and citizenship in contemporary China. Newly challenges parallels between hukou-based criminal justice system and Crimmigration in the developed countries; First systematic and holistic picture of Law-in-Action in urban China from unique access to government staff; Little scholarship on internal migration, particularly in the North, thus will contribute to growing the scope of Chinese migration studies
Keywords: Crime and Society; Prison and Punishment; Behavioral Sciences and Psychology; Asian Criminology; Crime-Sociological aspects; Corrections; Punishment; Psychology; Criminology